Long-Term Seismometric Monitoring of the Two Towers of Bologna (Italy): Modal Frequencies Identification and Effects Due to Traffic Induced Vibrations - Baraccani, Simonetta; Azzara, Riccardo M.; Palermo, Michele; Gasparini, Giada; Trombetti, Tomaso (Frontiers in Built Environment, 2020)
The rise of human activities and the constant increase of vehicles traffic in the cities, and in particular of heavy vehicles such as buses and trucks, causes continues ambient vibrations that can detrimentally affect the conservation of built artifacts, especially historical constructions. The effects of urban vibrations on buildings and monuments are far from being fully investigated. In general, peak levels of traffic-induced vibrations are rarely high enough to be the main cause of heavy structural damages. On the other hand, they contribute to the process of deterioration by adding extra stresses—through fatigue damage accumulation occurring as a result of long periods of exposure to low levels of vibration—or by contributing to soil densification—which can lead to the settlement of building foundations. As such, the estimation of threshold levels above which traffic-induced vibrations may cause damages to monumental buildings requires specific studies including long-time monitoring campaigns. Data from experimental campaign can, indeed, be used to extract information on the variation of dynamic properties of buildings, thus providing valuable pieces of information for a complete knowledge to plan effective preservation interventions. The present work aims to identify the effects of traffic induced urban vibrations on the two Towers of Bologna, particularly prone to fatigue-related damages and close to a high transit of vehicles, through a preliminary analysis of data from several dynamic monitoring campaigns conducted during the last years.